Las herramientas tecnológicas y el acceso al internet para el desarrollo de las actividades escolares en los estudiantes de la Unidad Educativa Replica Eugenio Espejo del cantón Babahoyo - García Vera, Emiro Daniel (2022)
With the massification of the use of the internet in virtual classes, its connectivity was complicated and its quality deteriorated, generating inconvenience among teachers and students who had to use it in the daily activities of their classes, which was also reflected in the use of the technological tools necessary to guarantee their normal application of educational platforms Faced with this situation, it is necessary to carry out the present study to show the main effects that the use of technological tools and access to the internet gender in the development of school activities for both teachers and students, their particular complications and other daily problems presented. The methodology to be used in the present case study is oriented to a qualitative design when studying qualities of the studied phenomenon and a descriptive approach since it is referred to when describing the results evidenced after the study and explanatory since it is expressed logically and sequentially. the development and results of the research work, using inductive methods when the part of a whole is to be studied and deductive when it is deduced from the whole to reach conclusions.